2000
DOI: 10.1063/1.1329863
|View full text |Cite
|
Sign up to set email alerts
|

Growth of large-scale GaN nanowires and tubes by direct reaction of Ga with NH3

Abstract: Large-scale wurtzite GaN nanowires and nanotubes were grown by direct reaction of metal gallium vapor with flowing ammonia in an 850–900 °C horizontal oven. The cylindrical structures were as long as 500 μm with diameters between 26 and ∼100 nm. Transmission electron microscopy, scanning electron microscopy, and x-ray diffraction were used to measure the size and structures of the samples. Preliminary results show that the size of the nanowires depends on the temperature and the NH3 flow rate. The growth mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(112 citation statements)
references
References 14 publications
3
107
0
Order By: Relevance
“…It has been reported that hydrogen has a higher surface mobility and can stream easier and faster than the products of GaN molecules. 26 Therefore, hydrogen has a higher tendency to occupy the surface defects on the substrate, which behave as heterogeneous GaN nucleation sites. When the GaN molecules encounter the surface defects created by hydrogen, the large number of nucleation sites enhances the probability of the random growth of GaN crystals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that hydrogen has a higher surface mobility and can stream easier and faster than the products of GaN molecules. 26 Therefore, hydrogen has a higher tendency to occupy the surface defects on the substrate, which behave as heterogeneous GaN nucleation sites. When the GaN molecules encounter the surface defects created by hydrogen, the large number of nucleation sites enhances the probability of the random growth of GaN crystals.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Ammonia was flowed at 50-100 sccm for 3-4 hours, resulting in a matrix of GaN nanowires and platelets on the nitride boat and quartz furnace liner. Typical nanowire dimensions are 20 µm to 100 µm in length and 100 nm to 400 nm in diameter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This recently reported growth technique [1] demonstrates processing of GaN one-dimensional structures as thin as 26 nm and up to 500 gm in length. This method is both interesting and attractive in that fabrication is carried out without the assistance of template materials as required by other methods.…”
Section: Introductionmentioning
confidence: 99%